THE SPACES OF CONTESTATION IN THE WORKS OF BOHUMIL HRABAL, MIRON BIAŁOSZEWSKI AND WOLFGANG HILBIG - Kledzik, Emilia (Porównania, 2012)
The article reports the state of research on the space in literature, starting with the findings of the structuralists, through semiotics, to anthropology and the spatial turn. It argues that the modern return of the space took place due to the popularity of the post-colonial theory in literary studies. The author adds a group of texts created in or in relation to the socialist’ times to the existing post-colonial interpretations of the Central European culture. The texts by Bohumil Hrabal, Miron Białoszewski and Wolfgang Hilbig, discussed using the carnival stylistics, create different spaces of contestation of the official discourse, which posses a subversive potential: a pub, railway stations and bazaars and the underground world of Berlin.